Hubungan Intake Protein dengan Status Gizi pada Remaja Puteri - Talitha Zulis iIslaamy; Ristya Widi Endah Yani; Farida Wahyu Ningtyias (Multidisciplinary Journal, 2021)
At the age of teenagers, students are more concerned with physical appearance. Adolescent girls are a group that is vulnerable to nutritional problems. Poor food intake is a common cause of nutritional problems in adolescents. A balance between the nutrients that enter is needed for optimal health. The data used in this study is a cross sectional design which aims to determine the relationship between protein intake and nutritional status in adolescent girls. Data collection on protein intake variables used a 24-hour food recall form. Data were collected on nutritional status variables using weight measurement with analytical digital scales and height measurements using microtoa. The sample used was 40 female students at MA Mambaul Khoiriyatil Islamiyah. The statistical test used is the Chi Square test. The percentage of respondents with less protein intake is 90%. The conclusion of this study is that there is a significant relationship between protein intake and nutritional status with a p value of 0.035 (<0.05). Keywords: Protein Intake, Nutritional Status, Adolescent Girls